The Correlation of Intraoperative Blood Pressure with Post Operative Nausea and Vomiting Incidence - Ni Wayan Eni Sukmawati; Ni Made Dewi Wahyunadi; Ni Putu J. Sastamidhyani (Inspirasi Foundation, 2022)
Objective: To determine the correlation of intraoperative blood pressure with PONV Incidence in post-general anesthesia patients at Tk. II Udayana Hospital Denpasar. Methods: This study employed analytical correlational with cross-sectional design. There were 60 respondents as the samples. The data were collected by using an observation sheet during intraoperative and PONV questionnaire. Data were analyzed using the Spearman's Rho test. Result: The result showed that the dominant of intraoperative blood pressure of the patient was normotensive (68,3%), the dominant of PONV incident was no PONV (90%). There was significant correlation of intraoperative blood pressure and PONV incidence (p-value <0.001) with coefficient correlation -0.507. Conclusion: There is a correlation of intraoperative blood pressure and PONV incidence on post general anesthesia patients at Tk. II Udayana Hospital Denpasar with strong correlation.